Profile of continuous use drugs prescribed in primary health care and presence in list of essential drugs - Paula Lorenzoni Nunes; Vanessa Adelina Casali Bandeira; Vanessa Boeira Flores; Andressa Oss-Emer Soares Bottega; Karine Raquel Uhdich Kleibert; Christiane de Fátima Colet (São Paulo State University (UNESP), 2021)
Objectives: To evaluate the profile of the drugs for continuous use prescribed in Primary Health Care (PHC) in Santa Rosa / RS and to identify presence in the official lists of essential drugs. Methods: Cross-sectional, analytical and quantitative study, with analysis of the digital prescriptions of users of primary health care in Santa Rosa. There was no gender restriction and patients who used at least one chronic drug were included. Data were collected through a printed report from users. Results: The study included 642 participants, with a mean age of 60.40±14.48, 64.3% were female and 47.4%, using polypharmacy. A total of 3.009 drugs were identified, with an average of 4.69±2.82 medications/prescription. There was a higher frequency of the cardiovascular system (46.9%), nervous system (16.8%) and digestive tract and metabolism (14.8%). The most commonly used drugs were hydrochlorothiazide, fluoxetine and omeprazole. Regarding the presence of drugs in the official lists, 90.9% are in RENAME and 90.8% in REMUME, and 80% of users have obtained full access to medicines. In the prescriptions, 0.3% contained antibiotics, 1.3% injectable drugs and all drugs were prescribed by the generic name and in a computerized way. Conclusions: The pharmacotherapeutic profile is similar to the national reality and most indicators are as recommended by the WHO, demonstrating the organization of the PA of the city, which facilitates the access of users to essential medicines. However, there was a high number of drugs per prescription and presence of polypharmacy, evidencing the importance of access to it as well as the promotion of the rational use of these drugs.